2013
DOI: 10.2147/ijn.s45439
|View full text |Cite
|
Sign up to set email alerts
|

Sn doping induced enhancement in the activity of ZnO nanostructures against antibiotic resistant S. aureus bacteria

Abstract: Highly ionic metal oxide nanostructures are attractive, not only for their physiochemical properties but also for antibacterial activity. Zinc oxide (ZnO) nanostructures are known to have inhibitory activity against many pathogens but very little is known about doping effects on it. The antibacterial activity of undoped ZnO and tin (Sn) doped ZnO nanostructures synthesized by a simple, versatile, and wet chemical technique have been investigated against Escherichia coli, methicillin-resistant Staphylococcus au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 31 publications
5
23
0
1
Order By: Relevance
“…From the FTIR spectrum, it was observed that the sharpness of Sn-O-Sn which is expected in the range of 610 cm⎯¹ to 640 cm⎯¹ as reported by Sudhaparimala et al [15] [21]. The presence of coupled oxide was indicated.…”
Section: Fourier Transformed Infra Red Spectroscopy(ftir)supporting
confidence: 53%
See 1 more Smart Citation
“…From the FTIR spectrum, it was observed that the sharpness of Sn-O-Sn which is expected in the range of 610 cm⎯¹ to 640 cm⎯¹ as reported by Sudhaparimala et al [15] [21]. The presence of coupled oxide was indicated.…”
Section: Fourier Transformed Infra Red Spectroscopy(ftir)supporting
confidence: 53%
“…But there are no reports available on the role play of the chemical constituents of aloe vera on the synthesis and properties of nano composite of tin (IV) oxide -Zinc Oxide. The present study is an attempt to explore the possibility of the same.The application of the oxides, ZnO, SnO2 and their combinations have been widely seen in the removal of organic contaminants, dyes in the form of photo catalyst and anti biotic [15]. Generally adsorption of dyes on the surface of tin oxide particles is indispensable for degradation of dyes with charges.…”
Section: Introductionmentioning
confidence: 99%
“…[63] Previous studies of NPs have shown that the greater the size of NPs, the greater the efficacy in inhibiting the growth of bacteria, involving both the production of ROS and the accumulation of NPs. [64] The high rate of generation of surface oxygen species from ZnO leads to the death of the bacteria once it kills/captures the bacteria. The ZnO NPs presumably remain tightly adsorbed on the surface of the leftover/dead bacteria preventing further antibacterial action.…”
Section: Maximum Bactericidal/fungicidal Concentration (Mbc/mfc)mentioning
confidence: 99%
“…We have used Fe as dopant for CeO 2 nanostructures owing to number of reasons; 1) it can induce ferromagnetism in CeO 2 nanostructures which is potential M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT spintronics and targeted cancer therapy [14], 2) It can reduce the band gap of CeO 2 nanostructures to great extent which is useful for their photodynamic activity [12] and 3) It can make possible fenton reactions, which helps in its photodynamic activity by producing large number of hydroxyl radicals [14,15] produced. This (DCFH-DA) assay can easily be oxidatively tuned into a fluorescent derivative because it is highly sensitive to ROS variation especially in an atmosphere containing the different factors like hydrogen peroxide, superoxide anion with other cofactors [16] Results and discussions…”
Section: Introductionmentioning
confidence: 99%